PENERAPAN PROSES DAN TEKNIK PERAMALAN – STUDI KASUS DI MANUFAKTUR TRANSFORMER - Elia Oey; Gabriella Karolina Ayrine (Jurnal Manajemen Industri dan Logistik, 2018)
Demand forecasting is essential for business processes and firm's profitability. A Good demand forecasting requires the expertise and reliability of the planning staff. The research is a case study in a transformer manufacturer in Indonesia, which planned to apply forecasting process and suitable tools for their products. The study demonstrated a systematic step required in forecasting the four studied products. For each product, 6 forecast models were evaluated and the best model was selected by optimizing forecast parameters which give the least forecast errors. The chosen forecasting model is a simple model but fairly complete in forecasting evaluation, to accommodate both trend and seasonal possibility in product forecasting. The study offers the basis for the company to establish forecasting processes and tools for its products. It also recommended the studied company to perform and monitor its forecasting process for continuous improvement to its business process.